Core PHP Programming, Third Edition - Atkinson, Leon (Prentice Hall PTR, 2011)
Core PHP Programming, Third Edition is the authoritative guide to the new PHP 5 for experienced developers. Top PHP developer Leon Atkinson and PHP 5 contributor/Zend Engine 2 co-creator Zeev Suraski cover every facet of real-world PHP 5 development, from basic syntax to advanced object--oriented development-even design patterns!